Penggunaan Media Pembelajaran Berbasis Augmented Reality Untuk Pengenalan Anatomi Tubuh Berbasis Android Di Sekolah Dasar - Acihmah Sidauruk; Mulia Sulistiyono; Muhammad Tofa Nurcholis (Batara Wisnu : Indonesian Journal of Community Services, 2023)
In the developing applications that utilize Augmented Reality (AR) technology, one of the most commonly used methods is to utilize special markers. The marker serves as a reference point to determine the position of digital objects in the real world. Augmented Reality is a term for an environment that combines the real world and a virtual world created by a computer so that the boundary between the two becomes very thin. The partner in this community service activity is SD Negeri Nogotirto which is an educational unit with an elementary level in Sleman, Yogyakarta. From the results of the interviews it was found that in Natural Sciences (IPA) lessons learning activities still use torso media (mannequins), also use learning videos such as YouTube and so on, therefore we need interactive media that can be used at school or at home in teaching and learning activities that can improve students' understanding of the human body anatomy introduction material used by the teacher to convey learning material to students. With the existence of an interactive learning media that can be used as an innovative example of science material which is then seen and felt by students, so that they better understand the learning material. The result of this community service is an Android mobile Augmented Reality application as a teaching medium about the process of introducing body anatomy in science lessons